Outcome of cranioplasty after decompressive craniectomy: Algorithm based study - Rijal, Suman; Nepal, Pankaj Raj; Bishokarma, Suresh; Devkota, Upendra Prasad (Nepal Journal of Neuroscience, 2018)
Cranioplasty is the next major surgical procedure that the patient undergoes following the decompressive craniotomy for severe traumatic brain injury (TBI). This study was designed with the objective to evaluate the outcome of our institutional algorithm-based protocol in the management of cranioplasty. This is aretrospective analytical study conducted in National Institute of Neurological and Allied sciences, Bansbari Kathmandu among 40 patients who underwent cranioplasty during a period of 5 years. Variables viz. postoperative CT changes, cranioplasty site infection and change in the modified Rankin scale following the cranioplasty were analyzed. Among 40 patients who underwent the cranioplasty, 82.5% were male and 17.5% were female. The age of the patients ranged from 4 to 72 years with mean of 29.5±13.13. Interval between primary decompression and cranioplasty ranged from 3 to 78 weeks. Algorithm based preoperative planning was done before cranioplasty. Previous abdominal bone fl ap preservation site infection was significantly associated (p value 0.048) with cranioplasty site infection. There was no deterioration in the MRS score. The proper evaluation of the preoperative CT scan and the combined adjunctive procedure with cranioplasty in the selected patients helps to decrease the post cranioplasty related complications.Nepal Journal of Neuroscience, Volume 15, Number 2, 2018, page: 36-40